2 Examining the Ring Theory of Personhood (RToP) strategy: Key components of dyssynchrony in end-of-life care. (14th March 2023) - Lim, Nicole-Ann; Ho, Chong Yao; Wong, Jeanette Shihui; Peh, Rachel Huidi; Abdul Rahman, Nur Diana; Chiam, Min; Xuelian Zhou, Jamie; Han Chan, Gene Wai; Koon Ong, Eng; Radha Krishna, Lalit Kumar
Abstract : Background: Current literature demonstrates palliative care physicians lack institutional support when assessing ethical and moral dilemmas in end-of-life care. Without a model to respond to dilemmas, physicians act on their subjective interpretations, contributing to greater risk of psychological morbidity and compromised patient care. Thus, an assessment model mapping physicians' self-concepts of personhood and identity will provide better support for distressed physicians. Methods: To obtain qualitative analyses of physicians' self-concepts of personhood and identity, we used the Ring Theory of Personhood (RToP) to design semi-structured interviews via the Systematic Evidence Based Approach (SEBA). 13 palliative care physicians with 8 to 18 years of palliative care experience were interviewed. Transcripts were thematically categorised using the RToP domains of personhood — Innate, Individual, Relational, and Societal, and synthesised using the Jigsaw Perspective. Results: Three main themes emerged — (1) Personal Principles, (2) Conflicts faced, and (3) Impact. Dyssynchrony between the 2 innermost (innate and individual) and 2 outermost (relational and societal) RToP domains was a central factor in influencing physicians' actions and experiences. Physicians utilise individual principles in navigating effective patient communication and care, affecting their capacity to confront situations challenging their beliefs. This either facilitates professional development or results in burnout and confidence loss. Generally, inadequate physician support begets detrimental adaptations and impacts. Conclusion: Providing holistic end-of-life care is directly impacted by physicians' emotional state, where dissonance throughout careers requires a longitudinal and personalised support system. Despite focusing on a single site, with restricted findings on the impact of sociocultural factors, our findings support the hypothesis that a standardised RToP tool should be constructed. This can ensure timely support for physicians struggling with dyssynchrony. Further implementation of this model in physician mentoring and counselling should be considered, preparing physicians for challenges within end-of-life care. Future studies should focus on designing the proposed RToP model.